A STUDY OF DISCOURSE PRACTICES AND IDEOLOGIES OF GENDER DIVERSITY IN THE ENGLISH-LANGUAGE NEWS COVERAGE OF INTERNATIONAL ONLINE ENTERTAINMENT MEDIA - Fangsaken, Boosaba (Journal of MCU Nakhondhat, 2025)
This research article aimed to study the discourse practices and ideologies of gender diversity in the English-language news coverage of international online entertainment media. It employed a qualitative research approach. The researcher used purposive sampling for linguistic data selection, where the linguistic data were specifically collected through the headlines of nine online entertainment media that report on gender-diverse groups: TMZ, People, Variety, CNN, Mashable, E-Online, Bet.com, Maxim, and The Hollywood Reporter. The data collection period was specified between 2016 and 2020. The results showed that the discourse practices of international online entertainment media comprised the following components of communication. The media construct texts or linguistic features in the headlines to disseminate information widely and reach a diverse audience. Then, communication is directed to the recipients, referring to individuals of all genders and ages who read news via the Internet. International online entertainment media aimed to communicate with the audience with two objectives: To represent the identities of gender-diverse groups and to reflect societal attitudes toward these groups. The ideologies and beliefs of gender-diverse groups emphasized pride in their identities and solidarity among those with similar sexual orientations. However, these groups continued to advocate for gender equality because the texts in news headlines often reflected societal perspectives that still perpetuated violations of rights and gender inequality.